Pengembangan Sistem Informasi Presensi Mahasiswa Memanfaatkan Teknologi QR-Code - Wahju Tjahjo Saputro; Krisna Widatama; Indra Ardiansyah (INTEK : Jurnal Informatika dan Teknologi Informasi, 2021)
The attendance of students of the Information Technology Study Program, University of Muhammadiyah Purworejo is currently still used and managed manually. In a manual system like this, it is very possible for errors in managing attendance data and student cheating in falsifying attendance at lectures. In the attendance process at the Information Technology Study Program using a manual system is considered less effective and less efficient.From these problems, it is necessary to create a student attendance system using a Quick Response Code with a WiFi area limit to prevent Information Technology students from Muhamadiyah Purworejo University outside of lectures or being absent from being able to fill in attendance or entrust attendance to friends and with this system, it is hoped that the process attendance can be done effectively and efficiently.The results of student attendance at the Information Technology Study Program, University of Muhammadiyah Purworejo. Quick Response Code with Wifi area limits has the ability to prevent manipulation of student attendance data and can recap computerized attendance data.